The Non-Existent May Cycle: Methods, Colonial Texts and Epigraphy - Péter Bíró (Journal de la Société des Américanistes)
The Non-Existent May Cycle: Methods, Colonial Texts and Epigraphy. More than three decades ago, Munro Edmonson suggested that Postclassic Yukatek Maya political organisation was based on a 256-year long may cycle, where each site competed to be the cycle seat. Several authors used this particular model to interpret diverse social and political patterns attested in Mesoamerican civilisations. In this paper, I examine Colonial Yukatek documents and epigraphy in order to look for the existence of such a cycle. Emphasising methodological issues of translations and interpretations of Colonial and pre-Hispanic texts and re-analysing several Chilam Balam passages, I suggest that Edmonson’s translation of the relevant sentences are incorrect. Also, I argue that such a word did not exist in Classic period inscriptions. Current ideas based on such a model should therefore be re-examined in light of these findings and other evidence should be used in order to prove their plausibility.